Implementasi Program Jemput Bola Administrasi Kependudukan (JEBOL ANDUK) Goes to School dalam Mempercepat Pelayanan Kartu Tanda Penduduk (KTP) Pemula - Ilham Wijaya, Muhammad; Hertati, Diana (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2025)
Surabaya, as the second largest metropolitan city in Indonesia with an area of 333.063 km² and a population of approximately 2.87 million, faces complex challenges in the implementation of population administration services. Data from the Surabaya City Population and Civil Registration Office (Dispendukcapil) in 2024 reveals a significant gap between targets and actual outcomes, where KTP ownership only reaches 46.68% of the eligible population. This condition indicates a discrepancy between public service theory which emphasizes accessibility and on-the-ground practices that remain hindered by conventional systems. This study aims to analyze the implementation of the